2018
DOI: 10.1007/s00259-018-4199-5
|View full text |Cite
|
Sign up to set email alerts
|

Yttrium-90 glass microspheres radioembolization (RE) for biliary tract cancer: a large single-center experience

Abstract: Purpose: Radioembolization (RE) is a promising treatment option for biliary tract cancers (BTC). We report here the largest series to date using this treatment modality. Methods: We retrospectively studied data from 64 patients treated outside prospective clinical trial at our institution. We studied baseline characteristics as potential prognostic factors. We studied dose delivered to the tumor as predictive factors of outcomes in patients not receiving concomitant chemotherapy. Results: The Progression-Free … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

4
40
0
3

Year Published

2019
2019
2022
2022

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(47 citation statements)
references
References 39 publications
4
40
0
3
Order By: Relevance
“…In the real-life setting, the European CIRT observational study [9] reports rates of 2.5% grade 3-4 AEs and the BSIR registry found 8% of all AEs to be above grade 3 in mCRC patients [21] as well as ICC patients [19]. The low rate of AEs \ 30 days following treatment (12% of the patients) presented in this study in addition to the low frequency of patients experiencing at least one treatmentrelated Grade C 3 SAEs in the overall patient cohort (16%), confirms the notion that TARE can be considered as a safe treatment alternative [22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 73%
“…In the real-life setting, the European CIRT observational study [9] reports rates of 2.5% grade 3-4 AEs and the BSIR registry found 8% of all AEs to be above grade 3 in mCRC patients [21] as well as ICC patients [19]. The low rate of AEs \ 30 days following treatment (12% of the patients) presented in this study in addition to the low frequency of patients experiencing at least one treatmentrelated Grade C 3 SAEs in the overall patient cohort (16%), confirms the notion that TARE can be considered as a safe treatment alternative [22][23][24][25][26].…”
Section: Discussionsupporting
confidence: 73%
“…To date, there is no evidence that the choice of glass versus resin microspheres has a significant impact on tumor response or survival [3,10,11,22]. However, Levillain et al showed that the efficacy of TARE in unresectable ICC significantly depends on the delivered tumor radiation dose.…”
Section: Discussionmentioning
confidence: 99%
“…Since the first reports, 90 Y radioembolization has been shown to be an effective method for both primary liver cancer, especially HCC, as well as secondary liver cancer, with the most existing evidence in metastatic colorectal cancer [8,9]. There is an increasing number of reports on the use of 90 Y radioembolization for intrahepatic cholangiocarcinoma, but the evidence of resin-based 90 Y microspheres in the treatment of unresectable and chemorefractory ICC is still limited [3,[10][11][12][13][14]. First results suggest that the median overall survival treating ICC with 90 Y radioembolization is 13.9 months (9.5-18.3 months), thus being at least as high compared to systemic chemotherapy, but potentially reduced side effects [3].…”
Section: Introductionmentioning
confidence: 99%
“…Bu tedaviler arasında yer alan Radyofrekans Ablasyon (RFA) ve Transarterial Kemoembolizasyon (TAKE) birçok merkez tarafından kullanılmaktadır. Transarteriyel Radyoembolizasyon (TARE) İKK'de lokal olarak kullanılan diğer bir tedavi yöntemidir 9 . Karaciğer dokusunun radyasyon hassasiyeti nedeniyle TARE yöntemi, selektif, internal olduğu için lokal ve güvenli bir yöntem olarak kabul edilmektedir 10 .…”
Section: Introductionunclassified
“…Y-90 -mikrosfer aktivitesi tümör yüküne göre, tek seans veya birden fazla seans uygulandı14 . Uygulamanın hemen ardından doğrulama yapmak için 24 saat içinde foton emisyonlu bilgisayarlı tomografi (SPECT) ile Y-90mikroküre birikimi takip edildi.Selektif internal radyoterapi olarak da bilinen transarteriyel radyoembolizasyon İKK de lokal olarak kullanılan transarteriyelbir tedavi yöntemidir9 . Karaciğer dokusunun radyasyon hassasiyeti nedeniyle TARE yöntemi lokal ve güvenli bir yöntem olarak kabul edilmektedir10 .…”
unclassified